Ultrasonography in infantile hypertrophic pyloric stenosis - Garg, S; Deka, PK; Chettri, PK; Tayal, A (Journal of College of Medical Sciences-Nepal, 2012)
Infantile hypertrophic pyloric stenosis (IHPS) is usually seen among the first born male infants. In recent time, ultrasonography has become the investigation of choice and has almost completely replaced the radiographic upper gastrointestinal series for the diagnosis of the disease. Here we report a case of 31 days infant with hypertrophic pyloric stenosis. Our purpose of reporting this case is to show the importance of ultrasonography in diagnosing infantile hypertrophic pyloric stenosis. DOI: http://dx.doi.org/10.3126/jcmsn.v7i1.5978 JCMSN 2011; 7(1): 73-76